FACTORS AFFECTING MORAL HAZARD BEHAVIOR IN VILLAGE FUND MANAGEMENT - Raza, Hendra; Nazaina, Nazaina; Idayanti, Lisa; Nur Ilham, Rico (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
This study aims to see the effect of accountability and transparency on the moral hazard of village funds with integrity as an intervening variable. This study uses primary data obtained directly from respondents by distributing questionnaires. The population in this study were all village officials in the East Angkola sub-district, amounting to 158 people. For the sampling technique using purposive sampling method, namely by having certain criteria where the criteria are village officials who are involved in managing village funds and serving at least one year. The results of this study indicate that accountability has no significant effect on moral hazard but has no effect on integrity, transparency has a significant effect on moral hazard but has no effect on integrity, while integrity has a significant effect on moral hazard. In addition, it was also found that integrity mediates the variables of accountability and transparency on moral hazard.